Real‐world uptake, safety profile and outcomes of docetaxel in newly diagnosed metastatic prostate cancer. (15th October 2017) - Rulach, Robert J.; McKay, Stephen; Neilson, Sam; White, Lillian; Wallace, Jan; Carruthers, Ross; Lamb, Carolynn; Cascales, Almudena; Marashi, Husam; Glen, Hilary; Venugopal, Balaji; Sadoyze, Azmat; et al.
Abstract : Objectives: To investigate the uptake, safety and efficacy of docetaxel chemotherapy in hormone‐naïve metastatic prostate cancer (mPC) in the first year of use outside of a clinical trial. Patients and Methods: Patients in the West of Scotland Cancer Network with newly diagnosed mPC were identified from the regional multidisciplinary team meetings and their treatment details were collected from electronic patient records. The rate of febrile neutropenia, hospitalisations, time to progression, and overall survival were compared between those patients who received docetaxel and androgen‐deprivation therapy (ADT), or ADT alone using survival analysis. Results: Of the 270 eligible patients, 103 received docetaxel (38.1%). 35 patients (34%) were hospitalised and there were 17 episodes of febrile neutropenia (16.5%). Two patients (1.9%) died within 30 days of chemotherapy. Patients who received ADT alone had an increased risk of progression (hazard ratio [HR] 2.03, 95% confidence interval [CI] 1.27–3.25; log‐rank test, P = 0.002) and had an increased risk of death (HR 5.88, 95% CI: 2.52–13.72; log‐rank test, P = 0.001) compared to the docetaxel group. The risk of febrile neutropenia was nine‐times greater if chemotherapy was started within 3 weeks of ADT initiation (95% CI: 1.22–77.72; P = 0.032). Conclusion: Docetaxel chemotherapy in hormone‐naïve mPC has significant toxicities, but has a similar effect on time to progression and overall survival as seen in randomised trials. Chemotherapy should be started at ≥3 weeks after ADT.